Changes in perceived uselessness and risks for mortality: evidence from a National sample of older adults in China - Yuan Zhao (BMC Public Health, 2017)
Abstract Background Self-perception of uselessness is associated with increased mortality risk in older adults. However, it is unknown whether and to what extent changes in perceived uselessness are associated with mortality risk. Methods Using four waves of national longitudinal data of older adults from China (2005, 2008, 2011, and 2014), this study examines the association between changes in perceived uselessness and risk of subsequent mortality. Perceived uselessness is classified into three major categories: high levels (always/often), moderate levels (sometimes), and low levels (seldom/never). Five categories are used to measure change over three-year intervals: (1) persistently high levels, (2) increases to moderate/high levels, (3) persistent moderate levels, (4) decreases to moderate/low levels, and (5) persistently low levels. Cox proportional hazard models were used to estimate mortality risk associated with changes in levels of perceived uselessness. Results Compared to those with persistently low levels of perceived uselessness, those with persistently high levels of feeling useless had 80% increased hazard ratio (HR) in mortality [HR =1.80, 95% CIs: 1.57–2.08, p < 0.001]; and those with increasing levels, persistently moderate levels, and decreasing levels of perceived uselessness had 42% [HR = 1.42, 95% CIs: 1.27–159, p < 0.001], 50% [HR = 1.50, 95% CIs: 1.32–1.71, p < 0.001], and 23% [HR = 1.23, 95% CIs: 1.09–1.37, p < 0.001] increased hazard ratio in mortality, respectively, when background characteristics were taken into account. The associations were partially attenuated when socioeconomic, family/social support, behavioral, and health-related covariates were individually taken into account. Older adults with persistently high and moderate levels of perceived uselessness still exhibited significantly higher risks of mortality (16% [HR = 1.16, 95% CIs: 1.00–1.135, p < 0.05] and 22% [HR = 1.16, 95% CIs: 1.06–1.139, p < 0.015], respectively) after adjusting for all covariates, although no significant mortality risks were found for either increasing to moderate/high levels or decreasing to moderate/low levels of perceived uselessness. Conclusions Persistently high and moderate levels of perceived uselessness are associated with significant increases in mortality risk. These findings have important implications for promoting successful aging in China.